2003
DOI: 10.1084/jem.20030298
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Inflammation and Airway Hyperresponsiveness in Immune-sensitized Mice by Dominant-Negative Phosphoinositide 3-Kinase–TAT

Abstract: Phosphoinositide 3-kinase (PI3K) is thought to contribute to the pathogenesis of asthma by effecting the recruitment, activation, and apoptosis of inflammatory cells. We examined the role of class IA PI3K in antigen-induced airway inflammation and hyperresponsiveness by i.p. administration into mice of Δp85 protein, a dominant negative form of the class IA PI3K regulatory subunit, p85α, which was fused to HIV-TAT (TAT-Δp85). Intraperitoneal administration of TAT-Δp85 caused time-dependent transduction into blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
189
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 230 publications
(193 citation statements)
references
References 53 publications
3
189
1
Order By: Relevance
“…[10][11][12] Several lines of evidence have suggested that SHIP-1, as a regulator of the PI3K pathway, might have a role in allergic response. In vitro studies have shown that SHIP-1 functioned as a negative regulator in mast cell degranulation in mouse cells 19 and human cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] Several lines of evidence have suggested that SHIP-1, as a regulator of the PI3K pathway, might have a role in allergic response. In vitro studies have shown that SHIP-1 functioned as a negative regulator in mast cell degranulation in mouse cells 19 and human cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, several recent studies have suggested that the PI3K pathway might also be involved in the T H 2 inflammatory response in mouse models of allergic asthma. 10,11 Either PI3K inhibitors 10 or expression of a dominant-negative PI3K subunit reduced the inflammatory response of the airway to antigen challenge. 11 The intracellular level of PIP3 is a critical point for regulation.…”
mentioning
confidence: 99%
“…Since IL-5 is a key cytokine responsible for eosinophil differentiation and survival [1,11], we determined in subsequent studies IL-5 levels in the BALF of c-maf-Tg and control mice. .…”
Section: Spontaneously Increased Eosinophilia Andmentioning
confidence: 99%
“…Increased numbers of CD4 + T cells expressing IL-4 and IL-5 have been found in the airways of asthmatic subjects [2]. Whereas IL-4 plays a central role in immunoglobulin E (IgE)-mediated responses, IL-5 is crucial for eosinophil recruitment and activation, which is observed during the late asthmatic reaction [3,9,11]. Th2 cells develop from naive T cells under the influence of IL-4 produced by Tand non-T cells such as IgE-activated mast cells [4,9].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, p110d-deficient B cells have major defects in activation by multiple stimuli in vitro, and blunted antibody responses in vivo [11][12][13]. Thus, while PI3K isoforms likely play distinct roles in B cells, T cells and neutrophils, their respective roles in regulating systemic cytokine production patterns, cell-mediated immunity and host defense functions remain unexplored.Several studies have shown that global inhibition of PI3K signaling using small-molecule inhibitors [14,15], antagonistic phosphatases [16] or cell-permeable antagonistic proteins [17] leads to a reduction of Th2-dependent airway inflammation in mouse models of allergic asthma. While these results implicate PI3K in asthma pathogenesis at some level, the cellular and molecular mechanisms are poorly understood, and the PI3K isoforms involved remain to be identified.…”
mentioning
confidence: 99%